Haemosporidian parasites and avian host population abundance in the Lesser Antilles. (11th February 2016) - Ricklefs, Robert E.; Soares, Leticia; Ellis, Vincenzo A.; Latta, Steven C.
Abstract: Aim: To determine statistical relationships between the prevalence of haemosporidian (malaria) parasites and the abundance of avian host populations across islands in the Lesser Antilles. Location: Thirteen islands in the Lesser Antilles, from Grenada in the south to St Kitts in the north. Methods: Birds were captured by mist net and small blood samples were taken for polymerase chain reaction and DNA sequencing analysis of haemosporidian parasite infections. Similarities between islands with respect to geographical distance, avian host assemblages and haemosporidian parasite assemblages were compared by partial Mantel tests. Relative abundances of avian host populations across islands were compared to the relative abundances of common haemosporidian lineages by stepwise regression. Results: Populations of parasite lineages were more heterogeneously distributed than were host populations across the islands; parasite lineages frequently shift between hosts on different islands and exhibit range disjunctions. Relative population sizes of two widespread and common species of bird in the Lesser Antilles, the bananaquit Coereba flaveola and the black‐faced grassquit Tiaris bicolor, were negatively related to the relative abundances of two parasite lineages, OZ01 ( Plasmodium sp.) and OZ12 ( Haemoproteus sp.), although the latter parasite was not recovered from either host. Positive associations between populations of Elaenia martinica and the relative abundance of three parasite lineages in populations of Vireo altiloquus additionally suggest the possibility of apparent competition between avian species mediated through haemosporidian parasites. Main conclusions: The results of these analyses are consistent with a strong influence of some avian haemosporidian parasites on populations of their hosts, including indirect interactions through apparent competition. In addition, the heterogeneity of host–parasite associations between islands suggests an evolutionarily dynamic system that is consistent with phases of host expansion and contraction, commonly known as the taxon cycle.